Pengaruh Sifat Termofisis Kaca Jendela Terhadap Suhu Radiasi Dalam Ruangan Akibat Paparan Sinar Matahari - Sangkertadi Sangkertadi; Alicia A.E. Sinsuw; Octavianus H.A. Rogi; Surijadi Supardjo; Ricky M.S. Lakat; Stepahanie J Najoan; Asni A. Nuchri; Rexvan L Podung (Sam Ratulangi University, 2025)
This paper describes the influence of thermophysical properties of building window glass on changes in radiation heat in a room due to sunlight on the window glass surface. From the various properties of glass, it is necessary to know which one has the greatest influence on the average radiation temperature in a room. This study uses a simulation calculation method by applying a steady-state heat transfer model using a spreadsheet and a computer program. In the calculation process, various variations of glass thermophysical properties are applied, including heat absorption coefficient, heat transmittance, heat reflectance, thickness and emissivity. In addition, the amount of solar radiation from 08.00 am to 04,00 pm was also varied with the case of tropical climates. The direction of the windows is varied facing North and West. The location of the building is at 1.50 North Latitude. The case is a typical office room measuring (6x6x2.5) m3, where the size of the window glass is considered full on the face facing the sky. The output is the temperature of the outer and inner glass surfaces, the temperature of the walls and floors in the room exposed to direct sunlight, and the average radiation temperature in the room. Visualization of the radiation heat emission pattern is also displayed using a heat transfer software. The simulation results show that the heat transmittance coefficient is the thermophysical property that has the most influence on changes in average heat radiation in the room. Meanwhile, the amount of heat absorption by glass has a significant effect on the surface temperature of the outer and inner glass areas. Keywords: Glass; Radiation; Tropical; Window